Umroh Backpacker: Prospek, Kendala Dan Strategi Pengembangannya - Kusumaningtyas, Menur (Media Mahardhika, 2018)
Umroh as one of the instruments of Islamic worship in Indonesia seems to be prospective compared to the others. The indication of its development is started in the practice of the law related to its such as Undang-Undang No. 13 of 2008 on the Implementation of Hajj ("UU 13/2008") as amended by Government Regulation in Lieu of Law No. 2 of 2009 ("Perpu 2/2009") furthermore, in terms of the growth rate and the potential of the majority of the population who are muslim in Indonesia, thus kind of travel will have opportunity to developee prospecttively. However, it doesnât mean that such travel should be operated without consideration is related to brand image. This journal attempts to discuss this travel and highlith both its prospect, its challenges, and its strategy.